Removal of heavy metals from wastewater using date palm as a biosorbent: a comparative review - M. Shafiq,; Alazba, A.A.; Amin, M.T. (Penerbit Universiti Kebangsaan Malaysia, 2018)
The drawbacks associated with activated carbon, mainly cost, have resulted in the continuing search for inexpensive adsorbents easily and abundantly available as waste materials. The current review presents the results of using different forms of date palm (DP) waste as low-cost biosorbents, highlighting effects of contact time, pH, the dose and size of the adsorbent particles, initial metal concentrations and the effects of pre-treatment on the adsorption efficiency of copper (Cu2+). The results of studies using the raw DP trunk fiber suggested the equilibrium time was approximately 2 h, with a significantly high removal of Cu2+ during the initial 1 h at acidic pH values of 5-6, which indicated the interference of H+ ions with metal ions at low pH values. The raw DP trunk fiber was tested with initial particle sizes of 75-251 μm and adsorbent dosages in the range of 0.4-5.0 g L-1. The best adsorption efficiency was obtained at the smallest particle size and the maximum dosage. The use of different initial Cu2+ concentrations resulted in a 10% decrease in removal, but the adsorption capacity was increased three-fold with an initial concentration of 20-100 mg L-1. A significantly higher removal efficiency of Cu2+ was achieved using the modified DP waste than with the raw trunk fiber for all experimental parameters and operational conditions owing to the increased functional groups on the modified adsorbents. The reviewed literature confirmed the efficiency of DP waste for the adsorption of heavy metals, but the use of the raw or even modified DP waste for the large-scale treatment of wastewater is still a concern owing to the cost effectiveness, availability and requirement for DP waste on a massive scale. Further research for physical modifications of the raw DP waste that employs cost-effective techniques, such as using the DP waste in the form of dehydrated carbon and media filters are required.